The syntax of applicative constructions in spoken Sudanese Arabic - Fazal Mohamed Mohamed Sultan; Mohammed Adam Mohammed Taha; Saeed Al- Qumairi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Different languages have different means for structuring clauses which allow the coding of a thematically peripheral argument or adjunct as a core-object argument. The resulting constructions are known as double object or applicative constructions. The primary aim of this paper is to present a syntactic analysis of applicative constructions in Sudanese Arabic within the theoretical framework of the Minimalist Program (Chomsky, 1993, 1995), in particular, the notion of phases, in combination with Pylkkänen's proposed phrase structure and the semantics of I-applicative (2000, 2008). The overall endeavor is to provide answers to the central questions: how applicatives in Sudanese Arabic are derived? Whether applicatives in Sudanese Arabic are I-applicatives or Eapplicatives? The derivation of such constructions in Sudanese Arabic involves the coding of new argument in the argument structure of the verb. This new argument is introduced via a preposition and has a benefactive/goal interpretation. This argument is c-commanded by any internal argument. The applied argument is placed in the complement position of the head ApplI, and can undergo neither A-movement nor wh-movement. This makes Sudanese Arabic fit into the general syntactic typology of I-type applicative languages cross-linguistically and consequently promoting contrastive linguistics.